Uyali aloqa vositalari talabalar o’rtasida qanchali foydalanishi, uyali aloqa vositalari inson organizmiga zararli ta’sirlari - Guzal Toshmatova, Nazarova Nasiba Islomqizi, Shuxratova Shaxnoza Rustam qizi, Akromova Mohina Baxromjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
A mobile phone now provides people not only with communication, but also with the services of a clock, calendar, calculator, mail, music, camera, video camera, radio, television, Internet, notepad, work schedule, etc. Through its small display, you can learn about events, happening around the world, send and receive messages and files to other phones via Bluetooth (even if the company has set communication restrictions), and secretly access someone's phone.